Analysis of the Coupling and Coordinated Development of Green Investment and Low Carbon Economy: Taking 16 Cities in the Yangtze River Delta Region as an Example - Yu, Nan; He, Feng; Amanguli, Maimaiti; Zhang, Xinyi; Zhou, Zejiong (International Journal of Global Economics and Management, 2024)
Firstly, based on the review of domestic and foreign scholars’ research on green investment and low-carbon economy, this article explores the coupling mechanism between green investment and low-carbon economy. Secondly, based on panel data from 16 cities in the Yangtze River Delta Economic Zone from 2015 to 2021, a comprehensive evaluation index system for green investment and low-carbon economy is constructed using five indicators: "low-carbon output indicator, low-carbon consumption indicator, low-carbon resource indicator, low-carbon environment indicator, and development capacity indicator." Furthermore, the entropy method is used to determine the weights of various indicators for green investment and low-carbon economy, calculate the comprehensive evaluation index for green investment and low-carbon economy in 16 cities in the Yangtze River Delta Economic Zone, and make a theoretical analysis of the development level of green investment and low-carbon economy in each region. At the same time, a coupling coordination model is used to explore the coupling degree and coupling between green investment and low-carbon economy index in 16 cities in the Yangtze River Delta Economic Zone from 2015 to 2021. Co scheduling. Finally, from the perspectives of time and space, in order to promote the coordinated development of green investment and low-carbon economy in the Yangtze River Delta Economic Zone, targeted policy recommendations are proposed for the government, enterprises, and the general public, with the aim of making theoretical contributions to the coordinated development of green investment and low-carbon economy, as well as the construction of ecological civilization in China.